ОПРЕДЕЛЕНИЕ КПД ПРИВОДА ЦЕНТРОБЕЖНОГО И ПОРШНЕВОГО КОМПРЕССОРА - Oleynik, Yuriy Anatolyevich; Prasko, Alexander Vladimirovich; Osmanova, Elena Georgievna; Naumenko, Svetlana (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2018)
adiabatic work of gas compression, friction losses in compressor bearings and gas pressure losses in the compressor. In the past, gas pressure losses in the compressor were not taken into account and these arise due to the friction of compressed gas flows, and due to the fact that the gas needs to overcome local resistances and the bends in compressor cavities. The computation formula of the coefficient of efficiency of the compressor was converted and it is used for a separate computation of the two coefficients of efficiency of the drive, in particular the coefficient of efficiency that takes into account the adiabatic work of gas compression and the friction losses in the bearings and the coefficient of efficiency that takes into account only gas pressure losses in the compressor. The plots for the coefficient of efficiency of the drive that takes into consideration only gas pressure losses in the compressor were constructed for centrifugal and piston compressors. Practical computations of the coefficient of efficiency of the drive that depends only on gas pressure losses in the compressor were done for centrifugal and piston compressors. For the centrifugal compressor this coefficient of efficiency can reach the value of 0.01 and for the piston compressor this value can be equal to 0.02. The values of the second order should be taken into account when calculating and estimating the coefficient of efficiency of the drive of centrifugal and piston compressors. Key words: the compressor, the compressor drive and the coefficient of efficiency.